KONSUMSI PANGAN MASYARAKAT INDONESIA ANALISIS DATASUSENAS 1999-2005 - Ariani, Mewa (GIZI INDONESIA, 2007)
Indonesia, in fulfilling the consumption of its people, is facing big problem causing by largenumbers of the people. This paper has objective to analyze the development of people’s foodconsumption after economic crisis. Data used is SUSENAS year 1999, 2002, 2003, 2004, and2005. The analysis was done in qualitative descriptive using tables. The result shows thateconomical recovery done by government has positive impact in increasing people’s foodconsumption in both quality and quantity. The food consumption is dominated by crops. Animalbased-foods and vegetables/fruits only reach 50 percent of the consumption expected. Everyregion has rice and wheat flour in staple food pattern. Only low-income-people have corn andcassava or sweet potato in their staple food pattern. Government policy should not only focus onmacro policy which oriented on economic growth and food security in national level, but alsoshould notice aspect of increasing general income of the people. The effort for increasing people’sconsciousness has to be done also in order to have diversified, nutritious, balanced, and secureas well as “halal” food consumption.Keywords: consumption, food, people, SUSENAS